Solution-processed ytterbium oxide dielectrics for low-voltage thin-film transistors and inverters. Issue 17 (1st December 2017) - Guo, Zidong; Liu, Ao; Meng, You; Fan, Caixuan; Shin, Byoungchul; Liu, Guoxia; Shan, Fukai
Abstract: High permittivity (high k) metal-oxide thin films fabricated via solution processes have recently received much attention for the construction of low-operating voltage and high-performance thin-film transistors (TFTs). In this report, amorphous ytterbium oxide (Yb2 O3 ) thin films were fabricated by spin coating and their applications in TFTs were explored. The physical properties of the solution-processed Yb2 O3 thin films processed at different annealing temperatures were systematically investigated using various characterization techniques. To explore the feasibility of the Yb2 O3 thin films as gate dielectrics for oxide TFTs, In2 O3 TFTs based on Yb2 O3 dielectrics were integrated. All the devices could be operated at 3 V, which is critical for the applications in portable, battery-driven, and low-power electronic devices. The optimized In2 O3 /Yb2 O3 TFT exhibits high electrical performances, including field-effect mobility of 4.98 cm 2 /V s, on/off current ratio of ~ 10 6, turn-on voltage around 0 V, and subthreshold swing of 70 mV/decade, respectively. To demonstrate the potential of In2 O3 /Yb2 O3 TFT toward more complex logic application, the unipolar inverter was further constructed.